2020
DOI: 10.1038/s41598-020-58967-8
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of a novel dehydratase of the fatty acid synthase type II critical for ketomycolic acid biosynthesis and virulence of Mycobacterium tuberculosis

Abstract: the fatty acid synthase type ii (fAS-ii) multienzyme system builds the main chain of mycolic acids (MAs), important lipid pathogenicity factors of Mycobacterium tuberculosis (Mtb). Due to their original structure, the identification of the (3 R)-hydroxyacyl-Acp dehydratases, HadAB and HadBc, of Mtb fAS-ii complex required in-depth work. Here, we report the discovery of a third dehydratase protein, HadD Mtb (Rv0504c), whose gene is non-essential and sits upstream of cmaA2 encoding a cyclopropane synthase dedica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 40 publications
4
18
0
Order By: Relevance
“…While most acyl sulfonamides ( 2 , 3 ) did not inhibit HadBC enzyme activity at 50 μM, acyl sulfonylureas ( 11 and 14 ) and oxadiazolone 12 showed moderate inhibition of HadBC at 50 μM (Table ). These results suggest that inhibition of HadAB rather than HadD likely accounts for the bactericidal activity of the compounds since HadD is nonessential . This is in agreement with a K157R mutation in HadC providing resistance to the compounds as it permits HadBC to functionally compensate for HadAB while being a lot less susceptible to the inhibition by these compounds …”
Section: Resultssupporting
confidence: 72%
See 1 more Smart Citation
“…While most acyl sulfonamides ( 2 , 3 ) did not inhibit HadBC enzyme activity at 50 μM, acyl sulfonylureas ( 11 and 14 ) and oxadiazolone 12 showed moderate inhibition of HadBC at 50 μM (Table ). These results suggest that inhibition of HadAB rather than HadD likely accounts for the bactericidal activity of the compounds since HadD is nonessential . This is in agreement with a K157R mutation in HadC providing resistance to the compounds as it permits HadBC to functionally compensate for HadAB while being a lot less susceptible to the inhibition by these compounds …”
Section: Resultssupporting
confidence: 72%
“…The HadD Mtb (Rv0504c) displayed a sequence identity of 100% with BCG_0547c (not shown); hence BCG_0547c will be referred to as HadD in the following text. HadD Mtb appears to catalyze the 3-hydroxyacyl dehydration step of late FAS-II elongation cycles during keto-MA biosynthesis . MSMEG_0948 (HadD) protein from M .…”
Section: Resultsmentioning
confidence: 99%
“…microti strains (OV254, ATCC 35782, 94-2272 and Maus IV) relative to M. tuberculosis H37Rv and BCG Pasteur control strains, we used an infection assay of SCID mice, as this model provides a rapid and sensitive method for evaluating the in vivo growth characteristics of mycobacterial strains during the acute phase of infection [31, 87–90]. This approach showed that all four tested M.…”
Section: Resultsmentioning
confidence: 99%
“…Subsequently, the authors showed that hadD deletion in M.tb resulted in a 63% reduction in keto-mycolic acids, while overexpression of hadD induced an 87% increase in keto-mycolic acids compared to wild type. Knockout mutants of hadD were attenuated in a murine model of infection, confirming hadD as a new target for drug discovery [107].…”
Section: Target Identificationmentioning
confidence: 86%